A Discourse Analysis of Lexical Cohesion on Naila Farhana’s Videos - Winda Wasalwa Batubara; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Moch. Imam Machfudi (Linguists : Journal Of Linguistics and Language Teaching, 2022)
The study sought to investigate the lexical cohesion in three YouTube videos by Naila Farhana, "Language Learning when you are an Introvert," "This useful language translation hack will help you!" and "Change your life! Benefits of Learning English Language". Farhana is known as an Indonesian YouTuber engaged in Languages. Through her video, the study analyzed Farhana's utterances on some topics based on lexical cohesion elements. Moreover, this study is concerned with Farhana's consistency, properly using lexical cohesion based, and finding out which lexical cohesion is the most dominant. Since to produce good writing and speech, it needs to pay attention when used to make the reader or listener not misunderstand. The research method was a qualitative description of the YouTube transcript to analyze the lexical cohesion devices. The results showed that the most dominant lexical cohesion of Farhana's three Youtube videos was Collocation of 36.93%. In addition, the study found Farhana's consistency in using lexical cohesion seen in the percentage of using the correct type of lexical cohesion reached from Halliday and Hasan's theory.